2016
DOI: 10.1289/ehp.1509676
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Particulate Matter Air Pollution Exposure and Mortality in the NIH-AARP Diet and Health Cohort

Abstract: Background:Outdoor fine particulate matter (≤ 2.5 μm; PM2.5) has been identified as a global health threat, but the number of large U.S. prospective cohort studies with individual participant data remains limited, especially at lower recent exposures.Objectives:We aimed to test the relationship between long-term exposure PM2.5 and death risk from all nonaccidental causes, cardiovascular (CVD), and respiratory diseases in 517,041 men and women enrolled in the National Institutes of Health-AARP cohort.Methods:In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
108
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(127 citation statements)
references
References 18 publications
16
108
3
Order By: Relevance
“…Although a meta-analysis using data from 22 European cohort studies reported no clear association between deaths from cardiovascular diseases and long-term concentrations of several PM metrics [64], many other studies have reported associations between long-term averages of air pollutant concentrations and increased cardiovascular mortality and morbidity [6572] or increased risks of coronary heart disease or coronary events [66, 73, 74]. As an example, in a study of 11 European cohorts, the risk of coronary events was increased by 13% for each 5 µg·m −3 increase in PM 2.5 .…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…Although a meta-analysis using data from 22 European cohort studies reported no clear association between deaths from cardiovascular diseases and long-term concentrations of several PM metrics [64], many other studies have reported associations between long-term averages of air pollutant concentrations and increased cardiovascular mortality and morbidity [6572] or increased risks of coronary heart disease or coronary events [66, 73, 74]. As an example, in a study of 11 European cohorts, the risk of coronary events was increased by 13% for each 5 µg·m −3 increase in PM 2.5 .…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…Epidemiological studies have confirmed that cardiovascular morbidity and mortality are closely related to atmospheric particulate concentrations (Brook et al 2010;Pope et al 2002Pope et al , 2009Thurston et al 2016). Atmospheric particulate matter (PM) is important carrier of toxic and harmful metal elements (such as Cr, As, Cd, Ni, Cu, Pb, Zn, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution is known to be a widespread public health concern due to enhanced morbidity and increased mortality rates associated with exposure (Costa et al, 2014;Tsai et al, 2014a;Chang et al, 2015;Thurston et al, 2015). The International Agency for Research on Cancer (IARC) of the World Health Organization (WHO) defined outdoor air pollution as carcinogenic to humans (Loomis et al 2013).…”
mentioning
confidence: 99%
“…Epidemiological investigations demonstrated that exposure to PM 2.5 increased the risk of developing respiratory diseases and lung cancer (Cui et al, 2015;Pope et al, 2011;Tsai et al, 2014b), as well as enhanced mortality and hospitalization rates for cardiovascular diseases (Chang et al, 2013, Chiu et al, 2014Lipsett et al, 2011;Thurston et al, 2015). Yang et al (2014) and Chiu et al (2014) showed that PM 2.5 exposure was associated with a higher frequency of stroke hospitalizations and mortality in humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation